The Potential Pitfall in Telework: Control and Deskilling Issues for Work Done at Home - Fulton, Crystal (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
An exploratory study of ten teleworkers revealed that while teleworkers choose this work option to improve their quality of life as workers and family members, they may not actually exercise much control over work processes. Familial obligations, interruptions, potentially problematic work environments, work routines of others, and isolation from coworkers in the traditional office work environment. . .